PERANAN KEPOLISIAN DALAM UPAYA PENEGAKAN DAN PEMBERANTASAN TINDAK PIDANA PENCURIAN HEWAN TERNAK DI POLRES ROKAN HULU - Gondi Wibowo; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Rokan Hulu is a district carved out of Kampar, Rokan Hulu district labeled as A Thousand Suluk where Rokan Hulu society in general are the majority of farmers and livestock farmers have. Here the expected role of the police to the police more effective, because the police is a government agency in charge of maintaining public order and security, especially in combating the crime of theft of livestock due to the theft of livestock in Rokan Hulu is still rife that every year has increased. The first goal of this thesis, the role of the police in enforcement and eradication of cattle theft in Police Rokan Hulu. Second, the constraints faced by the police in enforcement and eradication of cattle theft in Police Rokan Hulu. Third, the efforts of the police in enforcement and eradication of cattle theft in Police Rokan Hulu. This type of research is research Sociological law, because in this study the authors directly conduct research at the location where studied in order to give a complete and clear picture related problems examined. This research was conducted at the police station Rokan Hulu. Population and sample is the whole party related to the problem under study, the data source used, primary data and secondary data, data collection techniques in this study done by interviews, questionnaires and review of the literature. The results of the deliberations of the study it can be concluded: First, the role of the police in enforcement and eradication of cattle theft in Rokan Hulu Police Preventive action: providing legal counseling, supervising and observing the stranger whose actions are suspicious and remind each other in neighborhoods around while the repressive actions: follow-up report of the public and the police strengthen the function of the investigation. Second, the constraints faced by police Police Rokan Hulu is the limited number of police personnel, community negligence, trace the perpetrators, lack of information. Third, the efforts made to overcome these obstacles is to coordinate with the relevant legal institutions, raising public awareness, conduct legal counseling. Suggestions writer, so the police over again maximize the expected performance of the police more often provide counseling and guidance to jump into the community so that people can participate actively involved in providing assistance to the police in conducting any law enforcement process.Keywords: Role of the Police-Crime-Theft-Livestock